2021
DOI: 10.1016/j.heliyon.2021.e07958
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of emotional labour among employees of merged and acquired banks in Ibadan, South-West, Nigeria

Abstract: Mergers and acquisitions (M&As) are common among financial institutions. This process often exerts immense pressure on employees of these institutions. Hence, this study touches on the significant but neglected human angle aspect of M&A. Therefore, the study examined psychosocial predictors of emotional labour among employees of merged and acquired banks in Ibadan. The study design is cross-sectional, which involves using a quantitative data collection method to elicit responses from the participants. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
(56 reference statements)
0
5
0
2
Order By: Relevance
“…To examine the psychosocial predictors of emotional labor in merged banks in Ibadan, Nkemakolam et al (2021) employed convenience sampling to select seven (7) commercial banks that have been merged or acquired. The study found that job satisfaction, attitude towards M&A s, and acculturation were significant predictors of emotional labor both independently and jointly.…”
Section: Emotional Labour and Customers Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the psychosocial predictors of emotional labor in merged banks in Ibadan, Nkemakolam et al (2021) employed convenience sampling to select seven (7) commercial banks that have been merged or acquired. The study found that job satisfaction, attitude towards M&A s, and acculturation were significant predictors of emotional labor both independently and jointly.…”
Section: Emotional Labour and Customers Satisfactionmentioning
confidence: 99%
“…For instance, Asumah and Owusu (2021) argue that employees in the banking sector are required to express certain emotions, such as cheerfulness, friendliness, enthusiasm, warmth, calm, and confidence, when interacting with clients. Nkemakolam et al (2021) expressed that emotional labour is an important aspect in commercial banks given that most commercial banks nowadays emerged out of a merger and acquisition of banks. The rudiments of emotional labor practices may take a new shape and require urgent action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…African cross-border acquisitions shape change management mainly through four facets, namely, culture, relationships, motivation, and behavioural indicators (Van Niekerk et al, 2012). Organisational culture and societal culture influence stakeholder responses towards a cross-border change initiative (Nkemakolam et al, 2021). It is well known that successful change management is reliant on strong, interdependent stakeholder relationships, beneficial to the self, organisation, society, and community at large, with a clear emphasis on effective consultation and communication (Blom, 2018).…”
Section: Change Managementmentioning
confidence: 99%
“…Técnicas que cada día son empleadas por un mayor numero de empresas. Estudios similares pueden s er encontrados en [6,7,8].…”
Section: Introductionunclassified